Romania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper reviews the level and structure of tax revenues in Romania and proposes options to improve revenue mobilization drawing from other countries' experiences. Tax revenue in Romania is low compared with peers and has been declining over time. Strengthening the tax administration is crucial to improving tax collection efficiency in Romania, and requires commitment and ownership at the highest levels. Implementing and operationalizing new information technology infrastructure in Romania is a key priority, given its outdated and fragile systems. Romania should also conduct a comprehensive review of its tax system. This review would guide future reform needs in the area of tax policy with the primarily focus on improving revenue productivity and the growth-friendliness of the tax system.